FEATURES OF THE PREVENTION OF CARIES OF TEMPORARY TEETH IN CHILDREN IN THE MOUNTAIN REGIONS OF THE TRANSCARPATHIAN REGION - V.V. Shetelya (Український стоматологічний альманах, 2022)
The aim of the study. Rationale for early prevention of caries of temporary teeth in children who have been living in the mountainous regions of Zakarpattia region for a long time.